A review of the implementation of inclusive education in Zimbabwe: challenges and opportunities - Sibanda, Patrick (Pure and Applied Science Advances, 2018)
The purpose of this review was to, using literature, examine the various challenges faced in the implementation of inclusive education in Zimbabwe. Existing opportunities for the implementation of inclusive education were also explored. Literature indicates that challenges of implementing inclusive are more visible in sub-Saharan Africa than in the other parts of the world. The main challenges that were identified during review and synthesis of literature as affecting Zimbabwe in particular included lack of resources, inaccessibility of schools, ambiguity or complete lack of policies and laws, structural barriers, cultural stereotypes and negative attitudes, lack of political will, low teacher-pupil ratio, curriculum inaccessibility and research concerns. It also emerged from the review that opportunities such as the vast interest the government of Zimbabwe has invested in general education since 1980 which has culminated in the construction of several mainstream schools and training of specialist and special education teachers can be exploited for full inclusion of learners with disabilities. From the information gathered, the review concluded that the major causes of the many challenges affecting Zimbabwe are lack of political will, unclear policies and lack of funding. Meanwhile, the existing opportunities were seen to have potential for the successful implementation of inclusive education in Zimbabwe. On these bases, the review recommended mainly raising awareness among educational stakeholders, standardization of training, policy review, improved funding and restructuring of the implementation strategy.